Capacitance–voltage characteristics of sub-nanometric Al2O3 / TiO2 laminates: dielectric and interface charge densities. (1st June 2017) - Kahouli, Abdelkader; Elbahri, Marwa Ben; Lebedev, Oleg; Lüders, Ulrike
Abstract: Advanced amorphous sub-nanometric laminates based on TiO2 and Al2 O3 were deposited by atomic layer deposition at low temperature. Low densities of 'slow' and 'fast' interface states are achieved with values of 3.96 · 10 10 cm −2 and 4.85 · 10 −9 eV −1 cm −2, respectively, by using a 40 nm laminate constituted of 0.7 nm TiO2 and 0.8 nm Al2 O3 . The sub-nanometric laminate shows a low hysteresis width of 20 mV due to the low oxide charge density of about 3.72 · 10 11 cm −2 . Interestingly, such properties are required for stable and reliable performance of MOS capacitors and transistor operation. Thus, decreasing the individual layer thickness to the sub-nanometric range and combining two dielectric materials with oppositely charged defects may play a major role in the electrical response, highly promising for the application in future micro and nano-electronics applications.